1995
DOI: 10.1016/0014-5793(95)00959-d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of substituted phosphate triester alkyl lyso phospholipids (ALPs) as novel potential anti‐neoplastic agents

Abstract: Phosphate triester derivatives of the anti-neoplastic alkyi iyso phospholipid (ALP) have been prepared as novel potential therapeutic agents. In particular, symmetrical phosphate triesters have been prepared, using phosphorochloridate chemistry. The compounds have been fully characterised by a range of techniques, and assayed for their inhibition of DNA synthesis by mammalian cells in culture. The compounds are generally inhibitory towards DNA synthesis in the pM range. However, the magnitude of the effect var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Cytotoxicity was determined using the MTT assay (Marks et al 1992) or by thymidine incorporation, compounds (14-27) as previously reported (McGuigan et al 1994). For the MTT assay, compounds were dissolved into 11 mM stock solutions in ethanol or culture medium depending on solubility.…”
Section: Cytotoxicity Assay Protocolmentioning
confidence: 99%
“…Cytotoxicity was determined using the MTT assay (Marks et al 1992) or by thymidine incorporation, compounds (14-27) as previously reported (McGuigan et al 1994). For the MTT assay, compounds were dissolved into 11 mM stock solutions in ethanol or culture medium depending on solubility.…”
Section: Cytotoxicity Assay Protocolmentioning
confidence: 99%
“…The precedent figures illustrated the suppression of the phosphate moiety present in edelfosine thus producing cationic ether lipids. Another structural modification consisted in removing the cationic moiety and to substitute the phosphate function in order to isolate non-ionic ether lipids as reported by McGuigan et al in 1995 [ 188 ]. These non-ionic ether lipids were prepared by using 56.1 as starting material.…”
Section: Reviewmentioning
confidence: 99%
“…Drugs with these properties should be broad-spectrum antivirals, with low cytotoxicity and with reduced ability to select for resistance. Only one class of chemically synthesized compounds has been reported thus far to behave as a lipid-targeted membrane fusion inhibitor (15)(16)(17). However, the molecular mechanism underlying their antiviral activity is controversial (18).…”
mentioning
confidence: 99%